RANCANG BANGUN MODULAR FLOATING PONTOON FERROCEMENT SEBAGAI ALAT APUNG MULTIGUNA - Windyandari, Aulia; Zakki, Ahmad Fauzan (ROTASI, 2014)
Modular floating pontoon is a floating device commonly used as civil and marine construction. Pontoon is usually made of steel and high-density polyethylene (HDPE). Although the steel and HDPE has its own advantages and disadvantages in terms of economic, strength, and capacity. However the study of alternative raw materials for modular floating pontoon construction as multipurpose floating equipment is needed. Ferrocement which is familiar in the used for building construction material is an alternative material. Since the material is easy to find and it is such a versatile material that can be mass produced and has the mechanical strength that is simillar to steel and other materials. Following that condition the research is focused on the application of ferrocement technology for modular floating floating pontoon. The results show that the principal dimension of modular floating pontoon are length 80 cm, width 80 cm, height 75 cm, with the lightweight draft of pontoons is 30 cm. The material proportions for the modular floating pontoon are sand 48.2%, cement 34.5% and water 17.3%. Modular floating pontoon series consists of four Pontoons Square compiled with interlink (hook) so that the total of the package pontoon has a 160 cm long, 160 cm wide and 75 cm high.